Efecto de la edad de la reproductora sobre la morfometría del huevo y longitud corporal de la codorniz (Coturnix coturnix japonica) al nacimiento - Fuentes Neira, Nadia (2023)
The aim of this study was to determine the effect of the age of the quail (Coturnix coturnix japonica) on the morphometry of the egg and the size of the bird at birth. In total, 227 fertile quail eggs of three ages (15, 19 and 34 weeks) were used. Egg weight (g), shape index (%), hatching weight (g), body weight/egg weight ratio, and hatching length (mm) were evaluated using a completely randomized block design. There were no significant differences between ages with egg weight. Egg shape index was significantly higher in 15-week-old birds (79.50±0.34%) than in 34-week-old birds (78.0±0.36%; p<0.05). Birth weight was greater for 34-week-old birds (7.91±0.08 g) compared to 15-week-old birds (7.63±0.07 g; p<0.05). Live weight/egg weight ratio was significantly different between breeders of 15 (68.9±0.37%) and 34 weeks (70.4±0.41%), while quail length at hatch was greater in 19-week-old quail chicks (108±0.62 mm) It is concluded that the age of the breeding quail influenced all the variables evaluated, excepted egg weight.